Transformasi Digital dalam Hukum Acara Perdata: Tantangan dan Prospek Implementasi e-Litigation di Indonesia - Naya Indah Sahqia; Sidi Ahyar Wiraguna (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
Digital transformation in civil procedural law through the implementation of e-litigation in Indonesia offers procedural efficiency but faces significant normative and structural tensions. This study employs a normative-juridical approach to analyze the alignment of e-Court and e-Filing practices with civil procedural law principles, particularly the principles of legality, procedural fairness, and the right to a fair defense. Findings indicate that Indonesia’s current civil procedural framework still rooted in the colonial-era HIR and RBg does not explicitly recognize digital instruments, thereby creating legal uncertainty. Moreover, the effectiveness of e-litigation is hindered by juridical challenges (lack of explicit legal basis), technical barriers (uneven digital infrastructure and data security concerns), and social constraints (digital literacy gaps and limited access in remote regions). Without adaptive and inclusive reform of civil procedural law, electronic litigation risks excluding vulnerable groups and undermining substantive justice. This article recommends the enactment of a National Civil Procedure Code that is responsive to digital realities, in order to realize a judicial system that is efficient, transparent, and equitable in the digital era.